2017
DOI: 10.3892/mmr.2017.7454
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of keratinocytes to non-thermal dielectric barrier discharge plasma increases the level of 8-oxoguanine via inhibition of its repair enzyme

Abstract: Oxidative stress enhances cellular DNA oxidation and may cause mutations in DNA bases, including 8‑oxoguanine (8‑oxoG). Our recent study reported that exposure of cells to non‑thermal dielectric barrier discharge (DBD) plasma generates reactive oxygen species and damages DNA. The present study investigated the effect of non‑thermal DBD plasma exposure on the formation of 8‑oxoG in HaCaT human keratinocytes. Cells exposed to DBD plasma exhibited increased level of 8‑oxoG. In addition, mRNA and protein expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 33 publications
(44 reference statements)
2
15
0
Order By: Relevance
“…In this study, we investigated an intracellular ROS-generating system induced by DBD plasma and its mechanism in terms of epigenetic alteration in HaCaT human keratinocytes. Consistent with our previous reports [ [15] , [16] , [17] ], we demonstrated that exposure to DBD plasma induced the generation of ROS in HaCaT cells. The present study demonstrated that DBD plasma-induced ROS, such as superoxide anion and hydrogen peroxide, were generated via cellular NOXs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we investigated an intracellular ROS-generating system induced by DBD plasma and its mechanism in terms of epigenetic alteration in HaCaT human keratinocytes. Consistent with our previous reports [ [15] , [16] , [17] ], we demonstrated that exposure to DBD plasma induced the generation of ROS in HaCaT cells. The present study demonstrated that DBD plasma-induced ROS, such as superoxide anion and hydrogen peroxide, were generated via cellular NOXs.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, we have demonstrated that non-thermal dielectric-barrier discharge (DBD) plasma triggers complex signaling events that induce oxidative stress and endoplasmic reticulum stress by increasing ROS production [ [15] , [16] , [17] ]. Additionally, there are reports that cold, atmospheric plasma triggers H 2 O 2 and NO 2 production in cell culture media, thereby increasing intracellular ROS levels and modulating oxidative stress [ [18] , [19] ].…”
Section: Introductionmentioning
confidence: 99%
“…In the human mitochondria, OGG1 excises 8oxoG mispaired with adenine efficiently by catalyzing the splitting of an N-glycosidic bond between the damaged 8oxoG base and a deoxyribose sugar. OGG1 is the main enzyme for base excision repair (BER) of 8oxoG lesions [73]. DNA Pol γ plays a vital role in mtDNA replication [62] simultaneously involving Twinkle helicase and SSB.…”
Section: Mitochondrial Oxidative Stress and Mtdna Mutation Inmentioning
confidence: 99%
“…To evaluate the relationship between intracellular RONS and 8-oxoG formation, A549 cells were treated with the RONS scavenger N-acetyl-L-cysteine (NAC, Tokyo Chemical Industry) before plasma irradiation. 26,31,32) A549 cells at 50%-70% confluence were washed twice with D-PBS (−) and then loaded with 10 μM CM-H 2 DCFDA for intracellular RONS detection. The cells were incubated with 5 mM NAC in D-PBS (−) for 1 h at 37 °C in 5% CO 2 , and following trypsinization and resuspension in D-PBS (−), 1 ml of cell suspension (4.0 × 10 5 cells/ml) was irradiated with APPJ, and intracellular RONS and 8-oxoG were investigated as described in Sects.…”
Section: Pretreatment Of A549 Cells With a Rons Scavengermentioning
confidence: 99%
“…25) Kim et al reported that exposure of keratinocytes to non-thermal dielectric barrier discharge (DBD) leads to increased 8-oxoG levels. 26) Our previous report demonstrated that APPJ irradiation of A549 human lung carcinoma cells generates strand breaks and 8-oxoG formation in nuclear DNA. 24) The previous investigation revealed that although 8-oxoG formation is more readily induced than strand breaks, APPJ irradiation does not result in a notable reduction in cell viability 24 h after irradiation.…”
Section: Introductionmentioning
confidence: 97%